Effect of life style, taste, word of mouth, and brand trust to the purchasing decisions - Arif Syaifudin; Ufi Rumefi; Khamdan Suriyok (Junal Ilmu Manajemen, 2023)
The issues that are the focus of research are life style, taste, word of mouth and brand trust of Smart Education students. The population of this study were Smart Education students with a saturated sample technique of 107 respondents. The technique used to analyse the data is multiple linear regression test, classical assumption test, and hypothesis testing through F-test and t-test. Both simultaneously and partially, each variable of life style, taste, word of mouth and brand trust has a significant effect on the purchasing decisions of Smart Education students. It is hoped that producers can improve purchasing decisions by continuing to make variations and innovations in Samyang Hot Chicken products, so that they can be consumed more instantly and have more flavour variants.